Managing intraday liquidity: The Mexican experience - Biliana Alexandrova-Kabadjova; Francisco Sols-Robleda (Banco de México, 2013)
The present study calculates the proportional liquidity usage of the Mexican Real Time Settlement Payment System, SPEI, during a one month period. In particular, our interest is to get insights on how different is the liquidity level at the settlement in real time of low and large value payment transactions. To that end, we create an artificial environment, in which we use historical data from April 7 to May 7, 2010 and reproduce the operational conditions of SPEI. For each of these days, we arrange the transactions in four sets, delimited according to their value: all payments, payment orders with value higher than 100,000 MXN; transactions with value higher than 1,000,000 MXN and payments with value higher than 10,000,000 MXN. We measure the liquidity usage in different settings of settlement speed requirements. We find that among participants settlement strategies are heterogeneous. In particular, according to the size of the payment order, on weekly basis participants follow different patterns for settlement. Even further, payments within the same set are not homogeneously treated by banks.
Keywords: C63; G20; G28; 330; payment systems; intraday liquidity management; simulation